2015
DOI: 10.1159/000381426
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sweet Taste Receptor Gene Polymorphisms with Dental Caries Experience in School Children

Abstract: Sweet taste is a powerful factor influencing food acceptance. The peripheral taste response to sugar is mediated by the TAS1R2/TAS1R3 taste receptors. The aim of the study was to determine the relationship between TAS1R2 (rs35874116 or rs9701796) and/or TAS1R3 (rs307355) single nucleotide polymorphisms with dental caries experience in schoolchildren. A total of 184 schoolchildren aged between 7 and 12 years (101 girls, 83 boys) were included in the study. Genomic DNA was extracted from saliva samples and the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 49 publications
5
45
1
1
Order By: Relevance
“…Patients who are oversensitive may feel bitter or sweet taste more intensely, therefore they need a lower concentration of a substrate and, consequently, are less susceptible to caries [Darshana et al, 2014]. SNP of genes influencing taste reception, and thus carbohydrate metabolism, is a genetic factor in the aetiology of dental caries [Fushan et al, 2009;Wendell et al, 2010;Haznedaroğlu et al, 2015;Robino et al, 2015;Yildiz et al, 2016]. Hereditary fructose intolerance can lead to a variety of unpleasant symptoms, which occur in patients after its consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who are oversensitive may feel bitter or sweet taste more intensely, therefore they need a lower concentration of a substrate and, consequently, are less susceptible to caries [Darshana et al, 2014]. SNP of genes influencing taste reception, and thus carbohydrate metabolism, is a genetic factor in the aetiology of dental caries [Fushan et al, 2009;Wendell et al, 2010;Haznedaroğlu et al, 2015;Robino et al, 2015;Yildiz et al, 2016]. Hereditary fructose intolerance can lead to a variety of unpleasant symptoms, which occur in patients after its consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genetic and genomic studies have reported that a number of genes are associated with the susceptibility to dental caries [Louropoulou et al, 2008;Katz et al, 2009;Letra et al, 2012a Yang et al, 2013;Wang et al, 2013;Karasneh et al, 2014;Zorina et al, 2014;Haznedaroğlu et al, 2015]. However, some of these studies could not be replicated for validation in different populations [Louropoulou et al, 2008;Yang et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…Taste perception is believed to be influenced by cultural factors [Mennella et al, 2005]. Although not evaluated in the present study, it has previously been reported that sweet taste perception can be influenced by genetic factors [Haznedaroglu et al, 2015;Opal et al, 2015].…”
mentioning
confidence: 72%
“…Studies focusing on sweetness preference, sugar intake, and the levels of caries have been conducted in different countries [Jamel et al, 1997;Bretz et al, 2006;Robino et al, 2015]. Moreover, caries has been found to be associated with the sweet taste genetic factor [Haznedaroglu et al, 2015]. Genetic sensitivity to the bitter taste has been found to be related to caries experience [Rupesh and Nayak, 2006;Hedge and Sharma, 2008], and caries prevalence has been found to be higher in children of mothers who exhibit genetic taste sensitivity to sweet food [Alanzi et al, 2013].…”
mentioning
confidence: 99%